A Concurrent, Distributed Architecture for Diagnostic Reasoning - Cerri, Stefano a.; Loia, Vincenzo (User modeling and user-adapted interaction, 1997)
This paper demonstrates the feasibility of modeling concurrent diagnostic reasoning (CDR) by means of the computational model of actors. Actors have a value added on top of objects, because they include the properties of abstraction, modularity and reuse of objects but allow really concurrent and distributed architectures, in the sense that memory (the environment) is assumed not to be shared among actors. Whether concurrency really implies efficiency is still debated. We are more concerned here with the actor-based design of the diagnostic reasoning model. As a testimony of the feasibility of our proposal, a concrete, actor-based diagnostic program is presented as a module for an Intelligent Tutoring System in the domain of school algebra. CDR is obtained from the coordinated behaviour of actors which possess limited local knowledge and accomplish the global goal of diagnostic reasoning by interacting with each other. We examine how the `traditional' approaches to student modeling, such as overlay and bug models, can be re-visited in a distributed perspective of computational actors and how the latter view outperforms the previous ones.